Diversitas Sosiokultural: Penjelasan, Faktor, dan Manfaatnya dalam Masyarakat - Fauziyah Nasution; Aura Rahma Azzahra; Cindy Salsabila Ginting; Murni Amalia (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This article discusses sociocultural diversity and focuses on explanations, influencing factors, and benefits in society. Sociocultural diversity covers various aspects such as religion, language, social values ​​and norms, and gender. In a diverse society, sociocultural diversity can enhance creativity, broaden intercultural understanding, provide rich learning, build strong communities, and support sustainable economic growth. Through understanding, respecting and acknowledging this diversity, people can achieve an inclusive, just and harmonious life.